Medulloblastoma in a 6 Year Old Mixed Breed Dog: Surgical Debulking and Chemotherapy - Rachel Lampe; Miranda D. Vieson; Devon Hague; Dana Connell; Kari Foss; Kim A. Selting (Frontiers in Veterinary Science, 2019)
A medulloblastoma was surgically debulked from a 6 year old American Staffordshire Terrier, who then received a modified lomustine (CCNU), vincristine, procarbazine, and prednisolone (LOPP) protocol. The dog improved significantly and continued to do well until deterioration and euthanasia 5 months following surgery. This is the first known published case report of surgical cytoreductive surgery of a medulloblastoma in a dog with documented response to surgery and chemotherapy. Medulloblastoma is a primitive neuroectodermal tumor that is the most common malignant central nervous system (CNS) tumor in children, though it is less common in adults. This case illustrates the value of considering human literature when creating treatment plans for uncommon brain tumors in veterinary patients. Medulloblastoma should be a differential for cerebellar tumors in young to middle aged dogs, and surgery and chemotherapy should be considered.